PENTINGNYA PENGADAAN KARTU ANGGOTA PERPUSTAKAAN DI MTS GUPPI SAMATA - Kasmawati; Muliati; Khan, Sucy Nabila Ali; Halid, Muh.; Sofyan, Rahmat (Educational Leadership: Jurnal Manajemen Pendidikan, 2024)
Law of the Republic of Indonesia Number 43 of 2007 concerning Libraries which states that every school/madrasah maintains a national library that meets national library standards by taking into account national education standards. This study aims to describe the process of procuring library membership cards at MTs Guppi Samata by modifying and replacing the old card model. This study used a qualitative research method with observation guideline research instruments, interview guidelines, and documentation. Procurement of library membership cards is carried out starting from the design stage, filling in the data, and printing the cards. The procurement was carried out as a proof card that someone is a member of the library and to make it easier for librarians to record borrower data.